Two Northeast Pacific deep-water barnacle populations (Cirripedia: Calanticidae and Pachylasmatidae) from seamounts of the Juan de Fuca Ridge; "insular" endemics stemming from Tethys, or by subsequent dispersal from the Western Pacific center of distribution? - Newman, William A.; Jones, William J. (Zootaxa, 2011)
The first adults of the calanticid, Calantica moskalevi Zevina and Galkin, 1989, and specimens of a new pachylasmatine balanomorph genus and species, have been recovered by MBARI’s ROV Tiburon, from Juan de Fuca Ridge seamounts at 46º N – 130º W in the NE Pacific off Oregon, 1450 m and 2080 m depths, respectively. These two apparently allopathic populations evidently represent remnants of stocks most commonly confined to relatively deep waters around islands and occasionally continental margins of the Indo-West Pacific. These Juan de Fuca representatives can be inferred to be relicts of once broad Paleogene Tethyan populations rather than relatively recent immigrants by way of the NW Pacific. Apparently, the refugium afforded by seamount “islands” at bathyal and abyssal depths accounts for their survival in this relatively remote corner of Pacific Oceania.